DIGITAL BANKING UTILISATION CORRELATION TO FINANCIAL RESILIENCE, ARE INDONESIA AND INDIA DIFFERENT? - Irena Paramita Pramono; Riyang Mardini; Hasan Nashrullah; Ananya Thenaythodi; Al Ameen S (Kajian Akuntansi, 2025)
The swift increase in global internet users has driven the adoption of digital financial services, including online and mobile banking. Although several studies have explored the connection between financial inclusion and financial resilience, there is a paucity of literature specifically associating digital banking usage with individual financial resilience. This study seeks to examine the relationship between digital banking usage and financial resilience on a worldwide scale, with a particular focus on India. This study employed a quantitative methodology to evaluate cross-sectional data from the 2021 Global Findex Database, based on the completeness of the data, the samples collected in this study were from Indonesia with 196 samples, India with 280 samples, and the global data observed amounted to 25,844 samples. The analysis produced intricate correlational results. Both worldwide and Indonesian data revealed a statistically significant positive association (p < 0.05) between digital banking usage and financial resilience, but with a poor correlation strength (r < 0.3). This research indicates that digital banking correlates with individual financial resilience. Nonetheless, the Indian data revealed a distinct trend, specifically a notable albeit feeble negative correlation. This disparity signifies that the correlation between the two is significantly shaped by local context, such as digital product design, usage trends, or socioeconomic factors. This study indicates that the quantity of digital banking users in Indonesia and India remains inferior to the global average for digital banking usage. Further, the correlation of digital banking utilisation and financial resilience is considered weak, as mentioned above, digital banking utilization should not be regarded as a comprehensive or independent remedy for improving resilience.